Cycling Cross-Bridges Contribute to Thin Filament Activation in Human Slow-Twitch Fibers - López-Dávila, Alfredo Jesus; Chalovich, Joseph M.; Zittrich, Stefan; Piep, Birgit; Matinmehr, Faramarz; Málnási-Csizmadia, Andras; Rauscher, Anna Á.; Kraft, Theresia; Brenner, Bernhard; Stehle, Robert (Frontiers in Physiology, 2020)
It has been shown that not only calcium but also strong binding myosin heads contribute to thin filament activation in isometrically contracting animal fast-twitch and cardiac muscle preparations. This behavior has not been studied in human muscle fibers or animal slow-twitch fibers. Human slow-twitch fibers are interesting since they contain the same myosin heavy chain isoform as the human heart. To explore myosin-induced activation of the thin filament in isometrically contracting human slow-twitch fibers, the endogenous troponin complex was exchanged for a well-characterized fast-twitch skeletal troponin complex labeled with the fluorescent dye N-((2-(Iodoacetoxy)ethyl)-N-methyl)amino-7-nitrobenz-2-oxa-1,3-diazole (fsTn-IANBD). The exchange was ≈70% complete (n = 8). The relative contributions of calcium and strong binding cross-bridges to thin filament activation were dissected by increasing the concentration of calcium from relaxing (pCa 7.5) to saturating levels (pCa 4.5) before and after incubating the exchanged fibers in the myosin inhibitor para-aminoblebbistatin (AmBleb). At pCa 4.5, the relative contributions of calcium and strong binding cross-bridges to thin filament activation were ≈69 and ≈31%, respectively. Additionally, switching from isometric to isotonic contraction at pCa 4.5 revealed that strong binding cross-bridges contributed ≈29% to thin filament activation (i.e., virtually the same magnitude obtained with AmBleb). Thus, we showed through two different approaches that lowering the number of strong binding cross-bridges, at saturating calcium, significantly reduced the activation of the thin filament in human slow-twitch fibers. The contribution of myosin to activation resembled that which was previously reported in rat cardiac and rabbit fast-twitch muscle preparations. This method could be applied to slow-twitch human fibers obtained from the soleus muscle of cardiomyopathy patients. Such studies could lead to a better understanding of the effect of point mutations of the cardiac myosin head on the regulation of muscle contraction and could lead to better management by pharmacological approaches.